Impacts of Land Cover and Greenness Change on Soil Loss and Erosion Risk in Damota Area Districts, Southern Ethiopia - Mamush Masha; Teshome Yirgu; Mulugeta Debele (Applied and Environmental Soil Science)
Soil erosion is a key problem in Ethiopia in view of tropical climate, lack of vegetation, and landscape relief. Therefore, soil and water conservation (SWC) measures have been practiced, but their impacts on soil loss have not been estimated adequately. The RUSLE modeling was applied using satellite imageries, ASTER GDEM, rainfall, and soil data to estimate total annual soil loss for a 100 km2 hilly and highly populated area in Ethiopia. Soil loss decreased in the Damota districts from 21 to 13 million tons from 2000 to 2020. Similarly, the average annual soil loss decreased by 36%. Very slight-risk areas (< 5 t ha−1 yr−1) increased from 42.66 to 53.72%, and very high-risk areas (> 50 t ha−1 yr−1) decreased from 12 to 5%. Soil and water conservation measures showed an important implication against soil erosion through improved land cover and landscape greenness. However, still, the rate of soil erosion is high compared to the soil loss tolerance of 1–6 t ha−1 yr−1 for the Ethiopian highlands.